Grizzly night [videorecording (DVD)] - Bean, Bo; Mathewson, Katrina; Bean, Tanner; Call, Lauren; Esten, Charles, 1965-; Fehr, Oded, 1970- (Well Go USA Entertainment, 2026)
Based on true events. A rookie park ranger is thrust into the fight of her life after two deadly grizzly attacks happen on the same night by different bears. When a scream erupts outside a park chalet, panic spreads. The ranger must lead a rescue group of frightened tourists, campers, and park employees into the darkness, confronting the untamed wilderness and her own fears. This horrifying night of chaos forever changes the nation's understanding of wildlife forever.